Customer perception towards electric two-wheeler innovation - SANKAR, DR. JEGANATHAN GOMATHI; KUMAR. G, MR. HEMANTH (The journal of contemporary issues in business and government, 2020)
The research paper titled a study on customer’s perception towards electric two- wheeler. The objective of the study is to identify the factors that influence electric bikes purchase. Explanatory research is applied using convenience method of sampling with 145 respondents. The tools used of the study is frequency analysis, independent T-test, one-way ANOVA, regression analysis. It is found that factors related to customer perception are charging time, a smaller number of models, distance travelled for one full charge and environmental concern.